Flash Sterilization and Component Reimplantation Is a Viable Option for Articulating Antibiotic Spacers in Periprosthetic Knee Infections - Karas, Vasili; Rutherford, Richard W.; Herschmiller, Thomas A.; Plate, Johannes F.; Bolognesi, Michael P.; Joyce, Maria J.; Wellman, Samuel S. (The Journal of Knee Surgery, 2020)
The articulating antibiotic spacer is a treatment utilized for two-stage revision of an infected total knee arthroplasty. The original femoral component is retained and reused in one described variation of this technique. The purpose of this study is to determine the safety and efficacy of flash sterilization of the femoral component for reimplantation in an articulating antibiotic spacer for the treatment of chronic periprosthetic joint infection. A total of 10 patients were identified prospectively with a culture positive infected total knee arthroplasty. The patients underwent explantation, debridement, and placement of an articulating antibiotic spacer consisting of the explanted and sterilized femoral component and a new polyethylene tibial insert. The explanted tibial components were cleaned and flash-sterilized with the femoral components, but the components were then aseptically packaged and sent to our microbiology laboratory for sonication and culture of the sonicate for 14 days. Ten of 10 cleaned tibial components were negative for bacterial growth of the infecting organism after final testing and analysis. At 18-month follow-up, 9 of 10 of patients remained clear of infection. Among the 10 patients, 7 were pleased with their articulating spacer construct and had no intention of electively pursuing reimplantation. Also, 3 of 10 of patients were successfully reimplanted at a mean of 6.5 months after explantation. Autoclave sterilization and reimplantation of components may be a safe and potentially resource-sparing method of articulating spacer placement in two-stage treatment of PJI. Patient follow-up demonstrated clinical eradication of infection in 90% of cases with good patient tolerance of the antibiotic spacer.
Keywords: flash sterilization; articulating antibiotic spacer; total knee arthroplasty; periprosthetic joint infection